Special Issues in Hypertension - Berbari, Adel E.; Mancia, Giuseppe (Springer Milan : Imprint: Springer, 2012)
This volume is a cutting-edge review of the latest findings on key scientific and clinical issues in hypertension, with an integration of different new specific topics into the general knowledge of how to understand the pathophysiology and correctly diagnose and treat this chronic condition, which still represents the first cause of death in the world. Among the topics included in the book the reader will find some forms of hypertension which are frequently encountered in clinical practice and on which new important evidence is available, such as high-normal blood pressure (also termed pre-hypertension), white-coat and masked hypertension, and high blood pressure in the elderly and the very elderly. These emerging aspects are discussed in detail, along with chapters on issues of great current interest, such as the way to assess and how to treat asymptomatic organ damage, emerging cardiovascular risk factors such as short and long-term blood pressure variability, cognitive impairment and dementia. The book also deals with the changing concepts in the management of hypertension and antihypertensive pharmacotherapy, and addresses specific topics which are rarely discussed in clinical medicine volumes, including hypertension in post-menopausal women, hormonal replacement therapy, inflammatory disorders, sexual dysfunction with treatment, and the effect of Ramadan fasting on blood pressure. This ready to hand but encompassing volume proves to be a comprehensive updating tool to professionals and clinical practitioners managing patients with hypertension.